IMPACT OF COVID -19 ON INCOME OF THE TELLA SERASAN FOREST FARMER GROUP KPH BENAKAT PROVINCE OF SOUTH SUMATERA - Hidayat, Yayat; Lensari, Delfy; Junaidi, Junaidi (Universitas Muhammadiyah Palembang, 2021)
Social forestry provides an increase in the production and income of people in Tanggamus Regency as well as Kulon Progo Regency and Gunung Kidul Regency. KTH Tella Serasan also has a positive impact from the economic aspect, but with the covid 19 pandemic, members of the Tella Serasan Forest Farmers Group also experienced the impact of a decline in income, therefore further research was needed to what extent the impact of the COVID-19 pandemic on income for the community, especially the Tella Serasan Farmer Group. The purpose of this study was to analyze the impact of the COVID-19 pandemic on the income of the Tella Serasan Forest Farmer Group, Gelumbang District, Muara Enim Regency, South Sumatra Province. This research was conducted in December 2020 – April 2021. The research was conducted at Tella Serasan Teluk Limau Village, Gelumbang District, Muara Enim Regency, South Sumatra Province with the number of respondents in this study amounting to 54 respondents. The data Collected were primary data and secondary data. The income of the community before the Covid-19 pandemic in the plantation sector was Rp. 212,360,000 years/ha, livestock sector Rp.55,600,000/year and other sources of income Rp. 158.100.000/year. Community income during the COVID-19 pandemic in the plantation sector was Rp.144,335,000 year/ha, the livestock sector was Rp. 35.400.000/year, and other sources of income Rp. 127,835,000/year.